DEVELOPMENT MODEL TRAINING BALL HANDLING FOR BASKETBALL ATHLETE SENIOR HIGH SCHOOL (NDONESIA) - Fakhri Fajrin Kurniawan (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2020)
The goal of this research and development is to produce development model training ball handling basketball for basketball athlete Senior High School. This research and development also done to find out in depth about: increased mobility in basketball athlete Senior High School and know the success rate development model training ball handling basketball reviewed from : effective, efficient, traction, productivity of the athlete in doing ball handling basketball for basketball athlete Senior High School. This research and development uses qualitative and uses development research methods Research and Development (R & D) Borg W. R and Gall. M. D. which uses 10 stages of development. The steps in this development research start from the following : (1) Research and information collecting, (2) Planning, (3) Develop preliminary form of product, (4) Preliminary field testing, (5) Main product revision, (6) Main field testing, (7) Operational product revision, (8) Operational field testing, (9) Final product revision, (10) Dissemination and implementation. Subjects in research and development is basketball athlete Senior High School. The results of this effectiveness test model training are uses statistical test with formula before-after (pre-test and post-test). The result of the pre-test calculation resulted in 781 with average 50,39 while the post-test resulted in 818 with average 52,77. Thus it can be concluded that the use of development model training ball handling basketball athlete Senior High School is effective in improving the individual skills of basketball athlete Senior High School.